Analisis fatwa dewan syariah nasional No:98/DSN-MUI/XII/2015 tentang pedoman penyelenggaraan jaminan sosial kesehatan syariah dalam perspektif ekonomi islam (studi pada penyelenggaraan BPJS Kesehatan) - Rafiqi Rafiqi; Ridwan Ridwan; Jessica Pramudhita Rizkyka Senduk (Jurnal Paradigma Ekonomika, 2021)
This study aims to analyze the application of the National Sharia Council Fatwa No: 98/DSN-MUI/XII/2015 concerning Guidelines for the Implementation of Sharia Health Social Security in the Islamic Economic Perspective of the Health Social Security Administration Agency (BPJS). This type of research is descriptive qualitative research, a study that seeks to describe and explain the data obtained with secondary data. This study uses a library research approach, where the data sources are obtained from literature studies and various kinds of literature suitable for discussion, including the analysis of the fatwa of the Indonesian Ulema Council. This study indicates that the implementation of BPJS Kesehatan is not under the fatwa issued by the DSN-MUI according to the perspective of Islamic economics because it has not been maximized, and there are gaps in its implementation.